Expecting the Blessings of the Qur'an (Analysis of Surah As-Shad verse 29) - Gina Inshofiani Sugandi (Aslama: Journal of Islamic Studies, 2024)
Blessing is a very important role for human life. Because many people are looking for blessings in terms of sustenance, life, and so on. Therefore, the understanding of blessings needs to be studied again by collecting verses from the Koran about blessings that are realized in lecture assignments to become knowledge for those who still don't understand yet, a reminder for those who have forgotten. This research uses the thematic method (maudhu'i), an effort to interpret the verses of the Qur'an regarding a theme, by collecting all the verses that can represent and explain them as a whole to obtain answers or views of the Qur'an as a whole regarding that theme. The objects that will be studied are blessings on the Koran, blessings on people who believe and are pious, and blessings on places or countries. Based on the results of the author's study of several verses of the Koran. Blessings are all good deeds that cause benefits. If someone is guided by the Koran, he will receive blessings both in this world and in the afterlife. And if someone believes and is devoted to Allah and His Messenger, Allah will open the door to blessings from heaven and blessings from the earth.